2018
DOI: 10.1016/j.cdtm.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Tomato lycopene prevention of alcoholic fatty liver disease and hepatocellular carcinoma development

Abstract: Alcoholic liver disease (ALD) is a major cause of morbidity and mortality worldwide. The incidence of hepatocellular carcinoma (HCC) is increasing in the United States, and chronic, excessive alcohol consumption is responsible for 32%–45% of all the liver cancer cases in the United States. Avoidance of chronic or excessive alcohol intake is the best protection against alcohol-related liver injury; however, the social presence and addictive power of alcohol are strong. Induction of the cytochrome P450 2E1 (CYP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 129 publications
(337 reference statements)
0
20
0
1
Order By: Relevance
“…Thus, in European countries, the total intake of carotenoids varies from 9.5 to 16 mg/day (3 to 6 mg/day for β-carotene), vegetables and fruits being the main dietary sources [84]. In the United States, the average intake of lycopene varies from 6.6 to 10.5 mg/day for men and 5.7–10.4 mg/day for women, of which more than 85% of the intake comes from tomatoes and tomato products (salsa, pasta, soup, juice, and ketchup) [85]. The intake of carotenoids in diets in various countries is shown in Table 2 [40,84,86].…”
Section: Carotenoidsmentioning
confidence: 99%
“…Thus, in European countries, the total intake of carotenoids varies from 9.5 to 16 mg/day (3 to 6 mg/day for β-carotene), vegetables and fruits being the main dietary sources [84]. In the United States, the average intake of lycopene varies from 6.6 to 10.5 mg/day for men and 5.7–10.4 mg/day for women, of which more than 85% of the intake comes from tomatoes and tomato products (salsa, pasta, soup, juice, and ketchup) [85]. The intake of carotenoids in diets in various countries is shown in Table 2 [40,84,86].…”
Section: Carotenoidsmentioning
confidence: 99%
“…Genistein protects hepatocytes against toxicity due to creating a resistance to oxidative stress (75). Lycopene, an antioxidant found in red fruits such as tomatoes, inhibits hepatocyte apoptosis by reducing ROS levels and inhibiting mitochondrial dysfunction, and may have the ability to prevent FLD (76). It has been suggested that dietary intake of copper chloride and/or copper sulphate stabilizes SOD activity in an animal model, indicating a potential therapeutic benefit for FLD (77).…”
Section: Diet and Hepatocyte Protectionmentioning
confidence: 99%
“…Liver injury is a common clinical disease that has a wide range of detrimental effects on people's health, including liver cirrhosis, liver necrosis, fatty liver, liver cancer, and liver fibrosis (Chen, Chen, Lu, Wang, & Wang, 2015; Jiang et al., 2019; Liu, Xie, Li, Wu, & An, 2018). Many factors can lead to abnormal liver function, such as drugs, alcohol, and a range of chemical reagents (Fontana et al, 2010; Mitazaki et al., 2018; Shen et al., 2019; Stice, Xia, & Wang, 2018). Studies have shown that more than 350 drugs cause drug‐induced liver injury related to different clinical and pathological manifestations, mainly cholestasis, acute hepatitis, and acute liver failure (Björnsson & Hoofnagle, 2015; Massart et al., 2013; Ramachandran & Kakar, 2009; Watkins & Seeff, 2006).…”
Section: Introductionmentioning
confidence: 99%